Trust As a Means of Improving Corporate Governance and Efficiency - Chami, Ralph (IMF Working Papers; Working Paper, 2002)
Agency problems within the firm are a significant hindrance to efficiency. We propose trust between coworkers as a superior alternative to the standard tools used to mitigate agency problems: increased monitoring and incentive-based pay. We show how trust induces employees to work harder, relative to those at firms that use the standard tools. In addition, we show that employees at trusting firms have higher job satisfaction, and that these firms enjoy lower labor cost and higher profits. Finally, we show how trust may also be easier to use within the firm than the standard agency-mitigation tools.